2020
DOI: 10.1002/zaac.202000340
|View full text |Cite
|
Sign up to set email alerts
|

Structural Plasticity in the Frank‐Kasper Realm: Chemical Pressure Roles of the μ‐ and χ‐Phase Units in the Mo−Fe−Cr System

Abstract: Intermetallic phases have been known to exhibit a wide diversity since Pauling's seminal investigations into NaCd2 in the 1920s that, along with Cd3Cu4 and Mg2Al3, was shown by Samson to crystallize with a giant cubic cell containing >1000 atoms. The concept of structural plasticity – the notion that complex structures emerge from the release of internal stresses that would arise in simpler structures – has recently been used to account for one family of intermetallics, tracing the structures of Ca2Ag7, Ca14Cd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 61 publications
(75 reference statements)
1
13
0
Order By: Relevance
“…As we saw from the σ-phase, the fusion of D 3 h 15 and D 6 d 14 polyhedra offers substantial CP relief, while our examination of the ν-Mn 81.5 Si 18.5 structure points to a similar complementary match for T d 16 and D 6 d 14 polyhedra. The latter is confirmed by our earlier investigation of the origins of the μ-phase structure …”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…As we saw from the σ-phase, the fusion of D 3 h 15 and D 6 d 14 polyhedra offers substantial CP relief, while our examination of the ν-Mn 81.5 Si 18.5 structure points to a similar complementary match for T d 16 and D 6 d 14 polyhedra. The latter is confirmed by our earlier investigation of the origins of the μ-phase structure …”
Section: Discussionsupporting
confidence: 83%
“…46−49 In terms of the FK phases, CP analysis has previously accounted for the formation and elemental site preferences of the FK phases μ-Mo 6 Fe 7 and χ-Mo 5 Cr 6 Fe 18 . 50 Despite this progress, the mechanisms by which such packing effects shape the diversity of structures in this family of phases (and broader intermetallic chemistry) remain largely open. An important clue can be derived from their structures.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The Tl atoms are displaced away from the interface with the K-Au domains toward their remaining Tl neighbors, which were too distant in the KTl parent structure. This Tl-Au positive pressure also induces a twisting of the networks of Au 4 tetrahedra (corresponding to a soft phonon mode correlated with quadrupolar CP features in the Laves phases we previously investigated) [22,23,25]. This motion pushes the Au atoms away from the Tl-rich regions of the structure and toward K atoms with fewer short contacts to the Tl.…”
Section: Interpretation Of the Cp Schemesmentioning
confidence: 71%
“…For the expanded unit cell, the localized electron count for each site is tuned so that all the atoms experience equal negative atomic CPs, while for the contracted unit cell, these localized counts are adjusted so that all atoms bear the same amount of positive CP. We have found that using an average of the localized electron counts for each atom in the expanded and contracted auxiliary CP calculations leads consistently to physically meaningful CP schemes for the equilibrium structure [25,36].…”
Section: Calibrating the Localized Electron Countmentioning
confidence: 91%
See 1 more Smart Citation